2005
DOI: 10.1002/ptr.1622
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimycotic activity of some plant extracts towards yeast and yeast‐like strains

Abstract: As part of screening aimed at the selection of novel antimycotic compounds of vegetable origin, leaf extracts of Camellia sinensis L., Cupressus sempervirens L. and Pistacia lentiscus L. and the seed extract of Glycine soja Sieb. et Zucc. were tested against yeast and yeast-like species implicated in human mycoses. Of the extracts only those of C. sinensis (obtained from a commercial preparation of green tea) exhibited broad activity towards Candida glabrata, Clavispora lusitatiae, Cryptococcus laurentii, Filo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
1
23
0
2
Order By: Relevance
“…The denser texture would give a stickier perception to the panelists. In addition, Turchetti et al (2005) reported that GTE was able to inhibit the activity of yeast Saccharomyces cerevisiae (Strain DBVPG 6173), with its minimum inhibitory concentration (MIC) at 1006 lg/mL of total green tea polyphenols. The concentration levels of total tea catechins were approximately 533 and 1775 lg/g (wet basis) in the dough with GTE at 1.5 and 5.0 g/kg flour, respectively.…”
Section: Changes In Textural Characteristics: Hardness and Stickinessmentioning
confidence: 98%
See 1 more Smart Citation
“…The denser texture would give a stickier perception to the panelists. In addition, Turchetti et al (2005) reported that GTE was able to inhibit the activity of yeast Saccharomyces cerevisiae (Strain DBVPG 6173), with its minimum inhibitory concentration (MIC) at 1006 lg/mL of total green tea polyphenols. The concentration levels of total tea catechins were approximately 533 and 1775 lg/g (wet basis) in the dough with GTE at 1.5 and 5.0 g/kg flour, respectively.…”
Section: Changes In Textural Characteristics: Hardness and Stickinessmentioning
confidence: 98%
“…Subsequently, bread with smaller volume was produced that had relatively harder and denser texture, by which a relatively stickier texture would be perceived by the panelists when compared to the control. However, the model used in the study of Turchetti et al (2005) contained bio-medium that was much different from the bread dough model which is a multiphase system. Hence, further investigation of the effects of GTE on baker's yeast activity as well as amylase activity is necessary.…”
Section: Changes In Textural Characteristics: Hardness and Stickinessmentioning
confidence: 99%
“…Há registro que esta planta é utilizada como medicinal no município de Campos de Goytacazes -Rio de Janeiro (Pereira et al, 2004). Numerosos ensaios farmacológicos têm comprovado atividades antioxidante (Fiorini et al, 2005;Kalra et al, 2005), antiinfl amatória (Nag-Chaudhuri et al, 2005), hepatoprotetora (Fiorini et al, 2005), antimicrobiana (Yam et al, 1997;Turchetti et al, 2005), hipoglicemiante (Barbosa-Filho et al, 2005), inibidora da enzima conversora de angiotensina (Barbosa-Filho et al, 2006) e antimutagênica (Santhosh et al, 2005). Em razão desses efeitos, estudos procuram avaliar a efi ciência terapêutica da droga e dos metabólitos secundários para prevenção de câncer (Lambert;Yang, 2003;Halder et al, 2005) e osteoporose (Das et al, 2004), tratamento de diabetes (Gomes et al, 1995;Funke;Melzig, 2006), úlcera (Maity et al, 1995) e Alzheimer (Okello et al, 2004).…”
Section: Introductionunclassified
“…Consistent with this study, the leaf extract of C. sempervirens, which was determined to be rich in polyphenols expressed as quercetin glycosides (174 mg/mL) and biflavonoids (1460 mg/mL), did not exert any notable antifungal effect against a wide range of isolated strains of 24 yeast species from different countries (Candida albicans, C. glabrata, C. parapsilosis, C. tropicalis, C. zeylanoides, Pichia guilliermondii, Clavispora lusitaniae, Issatchenkia orientalis, Kluyveromyces marxianus, Saccharomyces cerevisiae, Yarrowia lipolytica, Cryptococcus laurentii, Filobasidiella neoformans, Prototheca wickerhamii, and P. zopfii) using an agar diffusion well bioassay [32]. The essential oil of the plant was evaluated another time for its antifungal activity against American type of culture collection strains of five food-spoilage yeasts, including C. albicans, Rhodotorula glutinis, Schizosaccharomyces pombe, S. cerevisiae, and Yarrowia lipolytica, and four fungus strains were notably inhibited by the essential oil with MIC values of 0.06-0.08 mg/mL, while it possessed moderate effect against Y. lypolytica (MIC ¼ 0.23 mg/mL) [33].…”
Section: Antimicrobial and Antiviral Activitymentioning
confidence: 98%